2021
DOI: 10.1111/neup.12764
|View full text |Cite
|
Sign up to set email alerts
|

LINC01123 potentially correlates with radioresistance in glioma through the miR‐151a/CENPB axis

Abstract: Radiotherapy represents the most effective nonsurgical therapy, whereas acquired radioresistance remains a major challenge in glioma treatment. Deregulation of long noncoding RNAs (lncRNAs) is frequently involved in tumorigenesis. This study investigates the role of LINC01123 in radioresistance in glioma with molecules involved. LINC01123 was identified as the most upregulated gene in a glioma gene expression dataset GSE103227. LINC01123 was highly expressed in the radioresistant glioma tissues radioresistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Supplementary Table S2 listed the lncRNAs involved in cancer radioresistance/radiosensitivity and their concise mechanisms. The sources of cancer included bladder cancer ( Tan et al, 2015 ; Jiang et al, 2017 ), breast cancer ( Liu et al, 2019a ; Zhang et al, 2019a ; Wang et al, 2019 ; Qian et al, 2020 ; Zhang et al, 2020a ), cardiac cancer ( Jia et al, 2019 ), gastric cancer ( Jiang et al, 2020 ; Lu et al, 2020 ; Xiao et al, 2020 ), cervical cancer ( Jing et al, 2015 ; Li et al, 2018a ; Han et al, 2018 ; Gao et al, 2019 ; Zhao et al, 2019 ; Wang et al, 2020a ; Ge et al, 2020 ), colorectal cancer ( Liu et al, 2020a ; Liu et al, 2020b ; Li et al, 2021 ; Liang et al, 2021 ), esophageal cancer ( Li et al, 2017 ; Chen et al, 2018a ; Zhang et al, 2019b ; Wang et al, 2020b ; Cheng et al, 2020 ; Liu et al, 2021a ; Sun et al, 2021 ; Yang et al, 2021 ), glioblastoma ( Li et al, 2018b ; Ahmadov et al, 2021 ; Li et al, 2022 ), glioma ( Yang et al, 2016 ; Zheng et al, 2016 ; Wang et al, 2020c ; Wang et al, 2020d ; Tang et al, 2020 ; Zheng et al, 2020 ; Gao et al, 2021 ; Tian et al, 2021 ), head and neck squamous cell cancer ( Li et al, 2020a ), laryngeal cancer ( Cui et al, 2019 ; Tang et al, 2019 ; Tang and Shan, 2019 ), nasopharyngeal cancer ( Jin et al, 2016 ; Wang et al, 2017 ; Ma et al, 2018 ; Yi et al, 2019 ; Han et al, 2020a ; Han et al, 2020b ; Wang et al, 2020e ; ...…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Table S2 listed the lncRNAs involved in cancer radioresistance/radiosensitivity and their concise mechanisms. The sources of cancer included bladder cancer ( Tan et al, 2015 ; Jiang et al, 2017 ), breast cancer ( Liu et al, 2019a ; Zhang et al, 2019a ; Wang et al, 2019 ; Qian et al, 2020 ; Zhang et al, 2020a ), cardiac cancer ( Jia et al, 2019 ), gastric cancer ( Jiang et al, 2020 ; Lu et al, 2020 ; Xiao et al, 2020 ), cervical cancer ( Jing et al, 2015 ; Li et al, 2018a ; Han et al, 2018 ; Gao et al, 2019 ; Zhao et al, 2019 ; Wang et al, 2020a ; Ge et al, 2020 ), colorectal cancer ( Liu et al, 2020a ; Liu et al, 2020b ; Li et al, 2021 ; Liang et al, 2021 ), esophageal cancer ( Li et al, 2017 ; Chen et al, 2018a ; Zhang et al, 2019b ; Wang et al, 2020b ; Cheng et al, 2020 ; Liu et al, 2021a ; Sun et al, 2021 ; Yang et al, 2021 ), glioblastoma ( Li et al, 2018b ; Ahmadov et al, 2021 ; Li et al, 2022 ), glioma ( Yang et al, 2016 ; Zheng et al, 2016 ; Wang et al, 2020c ; Wang et al, 2020d ; Tang et al, 2020 ; Zheng et al, 2020 ; Gao et al, 2021 ; Tian et al, 2021 ), head and neck squamous cell cancer ( Li et al, 2020a ), laryngeal cancer ( Cui et al, 2019 ; Tang et al, 2019 ; Tang and Shan, 2019 ), nasopharyngeal cancer ( Jin et al, 2016 ; Wang et al, 2017 ; Ma et al, 2018 ; Yi et al, 2019 ; Han et al, 2020a ; Han et al, 2020b ; Wang et al, 2020e ; ...…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al discovered that the elevated expression level of CENPB affects the chemotherapy response and prognosis of breast cancer patients through upregulation of targets in the Pi3k/Akt/mTOR signaling pathway [ 12 ]. Furthermore, studies have indicated that LINC01123 acts as a sponge for miR-151a, thereby upregulating CENPB expression to enhance the radioresistance of glioma cells both in vitro and in vivo [ 13 ]. What is worth noting is that current research has found that antibodies targeting CENPB can prolong the survival of breast cancer patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%